Opportunities of Modular Teaching - Jucevičienė, Palmyra (Acta Paedagogica Vilnensia, 1991)
The theoretical part of the article introduces the definitions of modular teaching as one of the most promising didactic systems, presents a brief history of the modular teaching, reveals its possible applications, the main principles of modular training are discussed in more detail. The empirical part of the article presents the results of a formative pedagogical experiment when modular teaching was applied at a higher education institution. According to them, it can be said that: 1) modular teaching is a complex system that helps achieve real parity relationship between teacher and students; 2) modular teaching allows complex personalization of the learning process; 3) modular programs and individual modules in the educational process help to achieve a high autonomy of students; 4) modular teaching enables a more efficient formation of the system of knowledge and skills in the process of vocational training; 5) the effectiveness of modular teaching according to different criteria is much higher than that of traditional didactical systems.